2012
DOI: 10.1100/2012/897697
|View full text |Cite
|
Sign up to set email alerts
|

Residues, Distributions, Sources, and Ecological Risks of OCPs in the Water from Lake Chaohu, China

Abstract: The levels of 18 organochlorine pesticides (OCPs) in the water from Lake Chaohu were measured by a solid phase extraction-gas chromatography-mass spectrometer detector. The spatial and temporal distribution, possible sources, and potential ecological risks of the OCPs were analyzed. The annual mean concentration for the OCPs in Lake Chaohu was 6.99 ng/L. Aldrin, HCHs, and DDTs accounted for large proportions of the OCPs. The spatial pollution followed the order of Central Lakes > Western Lakes > Eastern Lakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
(33 reference statements)
0
15
0
3
Order By: Relevance
“…β-HCH was the predominant HCH isomers in the shallow groundwater, and the β-/(α + γ)-HCH ratio of the 89% shallow groundwater samples were greater than 0.5. These observations indicated that the sources of the HCHs were mainly from the historical use of lindane after a period of degradation (Liu et al, 2012), an earlier study also demonstrated lindane was used in this region (Qiu et al, 2004). HCB has never been used directly as a pesticide in China, but has been used to produce pentachlorophenol (PCP) and pentachlorophenol-Na (PCP-Na), reagent and fireworks (Wei et al, 2007).…”
Section: Hchs and Hcbmentioning
confidence: 96%
“…β-HCH was the predominant HCH isomers in the shallow groundwater, and the β-/(α + γ)-HCH ratio of the 89% shallow groundwater samples were greater than 0.5. These observations indicated that the sources of the HCHs were mainly from the historical use of lindane after a period of degradation (Liu et al, 2012), an earlier study also demonstrated lindane was used in this region (Qiu et al, 2004). HCB has never been used directly as a pesticide in China, but has been used to produce pentachlorophenol (PCP) and pentachlorophenol-Na (PCP-Na), reagent and fireworks (Wei et al, 2007).…”
Section: Hchs and Hcbmentioning
confidence: 96%
“…The possible sources of HCHs in the environment are historical residues or recent inputs of industrial HCHs or lindane, which can be identified by their isomer ratios, such as ␣-/␥-HCH and ␤-/(␣+␥)-HCH (Iwata et al, 1993(Iwata et al, , 1995Willett et al, 1998;Walker et al, 1999;Liu et al, 2008;Liu et al, 2012;Ouyang et al, 2012;Wang et al, 2013a;Xu et al, 2013). The a-/␥-HCH ratio for technical HCH ranges from 4 to 7, while that for lindane is less than 0.1.…”
Section: Source Apportionment Of Ddxs and Hchs In The Spmmentioning
confidence: 99%
“…This indicates that the source of HCH might be the use of lindane (Yang et al 2010). The β-/(α+γ)-HCH ratio can be used to identify the history of HCH use, and 0.5 has been used as a threshold (Liu et al 2012). According to the analysis in the present study, the β-/ (α+γ) -HCH ratios of the all soil samples were 0.5, suggesting some recent use of lindane or the existence of an atmospheric source for the input (Liu et al 2012).…”
Section: Composition and Source Identificationmentioning
confidence: 99%